An analysis of cost-reduction innovation under capacity constrained inputs. Issue 6 (1st February 2019) - Nie, Pu-yan; Wang, Chan
ABSTRACT: This article focuses on duopoly cost-reduction innovation with the upstream input subjected to capacity constraints. By two-stage duopoly model, some interesting conclusions are achieved. Firstly, the higher efficiency firms invest the less in cost-reduction innovation and require the fewer resources under capacity constraints. Therefore, lower efficiency firms launch the lower price strategies. To our surprise, lower efficiency firms seem to be more aggressive both in innovation and in outputs. Secondly, symmetric firms' innovation decreases with the total resources while asymmetric firms' innovation increases with the total capacity. Finally, innovation gap decreases with both the total capacity and the degree of substitutability.